ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PADA BANK MUAMALAT INDONESIA PERIODE 2014-2022 - Aulia Rena Wengi; Lativa Hartiningtyas (JURNAL ILMIAH EDUNOMIKA, 2023)
Bank Muamalat is the first bank in Indonesia to use the concept of Sharia banking and officially operated on May 1, 1992 until now. The existence of Bank Muamalat, which is known as the pioneer of the establishment of Islamic banking in Indonesia, certainly deserves to be assessed for the health of its financial performance. Profitability is one of the right indicators to measure company performance because a company's ability to make a profit can be a benchmark for a company's performance. Bank Indonesia has determined that one of the measures of profitability of a bank is Return on Asset (ROA). The financial ratios that affect ROA are CAR, FDR, NPF and BOPO. The purpose of this study was to determine the effect of NPF, FDR and BOPO on the Profitability (ROA) of Bank Muamalat Indonesia. This research uses a quantitative approach with an associative type of research. The sampling technique used is non probability sampling by purposive sampling. The sample in this study is data on the quarterly financial ratio report of PT Bank Muamalat Indonesia starting from the first quarter of 2014 – third quarter of 2022 with a total of 35 samples. The results showed that NPF did not have a significant effect on profitability (ROA), FDR had a positive and significant effect on profitability (ROA) and BOPO had a negative and significant effect on profitability (ROA) and NPF, FDR and BOPO simultaneously had a positive and significant effect on profitability (ROA).